Aortic aneurysm mimicking a right atrial mass. Issue 10 (4th September 2016) - Mohamed, Ahmed; Elsayed, Mahmoud; Kalra, Rajat; Bulur, Serkan; Nanda, Navin C.
Abstract : We present a case of a 54‐year‐old female who was initially thought to have a cystic mass in the right atrium on two‐dimensional transthoracic echocardiography. Careful transducer angulation and off‐axis imaging showed this mass‐like effect was produced by an aortic root aneurysm impinging on the right atrium.